Ex-PAN carbon fibers vs carbon nanotubes fibers: From conventional epoxy based composites to multiscale composites. (September 2018) - Lutz, V.; Duchet-Rumeau, J.; Godin, N.; Smail, F.; Lortie, F.; Gérard, J.F.
Graphical abstract: Highlights: Coupling of single fiber fragmentation test with acoustic emission. Comparison of two routes to introduce carbon nanotubes in fiber reinforced composite. Multiscale Characterization of interfaces by Raman spectroscopy and microscopy. Abstract: In order to design multiscale and multifunctional composites, synergy between carbon nanotubes and conventional carbon fibers was investigated. Two routes were compared to introduce carbon nanotubes into epoxy-carbon fibers composites either grown onto ex-PAN carbon fibers or directly under the form of carbon nanotubes (CNT) fibers. The multiscale composites were compared with conventional ones based on commercial ex-PAN carbon fibers. The interfacial interactions between fibers and matrix were mechanically characterized by the single fiber fragmentation test (SFFT). Suitable microstructure observations combined with acoustic emission were fruitful to identify morphological damages. In contrast to conventional or even CNT modified carbon fiber based composites, superior mechanical properties were reported for continuous CNT fibers reinforced composites. Interactions at the molecular scale between CNT network and macromolecular chains probed by Raman spectroscopy are responsible of the high stress transfer efficiency and demonstrate that these CNT fiber-based composite materials remain very promising for structural applications.